VISUALISASI DAN ANALISIS KONDISI KEUANGAN DAERAH KABUPATEN BENGKALIS TAHUN 2020-2024 BERDASARKAN MODEL ENAM DIMENSI - Saputri, Anniza; Muttaqin, Husnul (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research analyzes the financial condition of Bengkalis Regency from 2020-2024 using Ritonga's Six Dimensions Model amid high dependency on central transfers in resource-rich regions. The objective is to measure fiscal health through multidimensional ratios and visualize trends via Power BI dashboards. Employing descriptive quantitative methods, the population comprises all annual LKPD and APBD realization reports (5 units), sampled via total sampling. Instruments include secondary data processed with Power Query, Data Model, and DAX formulas, analyzed through ratio calculations, composite index aggregation, and interactive visualizations. Results reveal declining short-term solvency (Ratio A: 6.83 to 0.01) and financial flexibility (Ratio B: 204.69 to 7.79), with IKK dropping from 6.21 (good) to 0.74 (adequate). In conclusion, Bengkalis requires PAD optimization and cash management reforms for fiscal sustainability.